HBR's 10 must reads 2021 : the definitive management ideas of the year from Harvard Business Review. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2020)
"A year's worth of management wisdom, all in one place. We've combed through the ideas, insights, and best practices from the past year of Harvard Business Review to help you get up to speed fast on the relevant concepts driving business today. Discover new ideas and sample the latest thinking of our vast array of management experts. Revisit these topics now to make sure your organization is incorporating the best, most up-to-date practices, or keep this book as a reference so you can turn to these memorable pieces when you need them the most. The collection includes articles on leadership, strategy, and innovation, as well as articles that will help you manage yourself and others. HBR's 10 Must Reads paperback series is the definitive collection of books for new and experienced leaders alike. Leaders looking for the inspiration that big ideas provide, both to accelerate their own growth and that of their companies, should look no further. HBR's 10 Must Reads series focuses on the core topics that every ambitious manager needs to know: leadership, strategy, change, managing people, and managing yourself. Harvard Business Review has sorted through hundreds of articles and selected only the most essential reading on each topic. Each title includes timeless advice that will be relevant regardless of an ever-changing business environment"--
The feedback fallacy / by Marcus Buckingham and Ashley Goodall -- Cross-silo leadership / by Tiziana Casciaro, Amy C. Edmondson, and Sujin Jang -- Toward a racially just workplace / by Laura Morgan Roberts and Anthony J. Mayo -- The age of continuous connection / by Nicolaj Siggelkow and Christian Terwiesch -- The hard truth about innovative cultures / by Gary P. Pisano -- Creating at trans-inclusive workplace / by Christian N. Thoroughgood, Katina B. Sawyer, and Jennica R. Webster -- When data creates competitive advantage... / by Andrei Hagiu and Julian Wright -- Your approach to hiring Is all wrong / by Peter Cappell -- How dual-career couples make it work / by Jennifer Petriglieri -- Building the AI-powered organization / by Tim Fountaine, Brian McCarthy, and Tamim Saleh -- Leading a new era of climate action / by Andrew Winston.
Includes index.
Description based on online resource; title from digital title page (viewed on December 30, 2020).
Master record variable field(s) change: 050
Keywords: Management; Management; elektronické knihy; electronic books